Transport parameters of macroscopic continuum model determined from discrete pore network simulations of drying porous media: Throat-node vs. throat-pore configurations. (21st September 2020) - Lu, Xiang; Kharaghani, Abdolreza; Tsotsas, Evangelos
Highlights: Configurations of throat-pore and throat-node models for drying are simulated. Drying kinetics and liquid structure obtained from both models are compared. Volume-averaged data is exploited to determine the moisture transport coefficient. The continuum model of drying is revisited by pore network simulations. Abstract: In this work, the volume-averaged transport parameters of one-dimensional macroscopic continuum model for drying is determined from three-dimensional microscopic discrete pore network models. The discrete models are called throat-node model (TNM) and throat-pore model (TPM) and the respective drying simulations are carried out under identical initial and boundary conditions. In the first place, the predictive capabilities of these two discrete models are compared. The void space is overestimated by the TNM when the mean radius of throats and pores is larger than 100 µm. The drying time of TPM is found to be less than half of the simulated drying time from TNM. Next, the continuum model parameters are computed based on the simulation results obtained from these two different pore network models. Two functions between the spatially-averaged local partial vapor pressure and the saturation vapor pressure as well as the moisture transport coefficient are determined. Profiles of moisture transport coefficient can be divided into three regions by two critical saturation values – the saturation of maximum interfacial area and turning point saturation. The partial vapor pressure in the two-phase region deviates from the saturation vapor pressure, considered as a non-local equilibrium effect. Such an effect is observed for both network configurations but is less pronounced for TPM. Finally, feeding these parameters to the continuum model can predict the characteristics of the drying process, bridging the gap to the macroscale.